When she woke : a novel - Jordan, Hillary, 1963- (Chapel Hill, N.C. : Algonquin Books of Chapel Hill, 2011)
In the future, abortion has become a crime as a series of events threatens the existence of the United States. One woman wakes up to discover that her skin color has been changed to red as punishment for having the procedure done. Now she must embark on a dangerous journey in order to find refuge from a hostile and threatening society.
Lariat Reading List, TLA 2012
Keywords: Dystopias -- Fiction; Political fiction